A systematic analysis of star cluster disruption by tidal shocks: I. Controlled N-body simulations and a new theoretical model - Webb, Jeremy J.; Reina-Campos, Marta; Kruijssen, Diederik (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. Understanding the evolution of stellar clusters in an evolving tidal field is critical for studying the disruption of stellar clusters in a cosmologi
Gesehen am 03.06.2019